First reports of parental care in species of the genus Dismegistus (Hemiptera: Heteroptera: Parastrachiidae) - Jerzy A. LIS; Paweł J. DOMAGAŁA (European Journal of Entomology)
Parental care is reported in several insect orders. Usually, it involves protecting eggs, burying them, moving a batch of eggs from place to place and feeding the larvae. Insect parental care is well developed in Heteroptera and is particularly widespread in the superfamily Pentatomoidea. The species best known for their maternal care belong to the subfamily Sehirinae (Cydnidae) and the genus Parastrachia (Parastrachiidae). There are no published data on parental care in species of the genus Dismegistus (the second genus within the family Parastrachiidae). This paper provides the first reports of females of species of Dismegistus carrying and guarding egg batches in the same way as species in the genus Parastrachia and certain Sehirinae.